The Intergenerational Transmission of Automobile Brand Preferences1. (December 2015) - Anderson, Soren T.; Kellogg, Ryan; Langer, Ashley; Sallee, James M.
Abstract : We document a strong correlation in the brand of automobile chosen by parents and their adult children, using data from the Panel Study of Income Dynamics . This correlation could represent transmission of brand preferences across generations, or it could result from correlation in family characteristics that determine brand choice. We present a variety of empirical specifications that lend support to the former interpretation and to a mechanism that relies at least in part on state dependence. We then discuss implications of intergenerational brand preference transmission for automakers' product‐line strategies and for the strategic pricing of vehicles to different age groups.